Antifungal activity of glyphosate against fungal blast disease on glyphosate-tolerant OsmEPSPS transgenic rice. (October 2021) - Mehta, Sahil; Kumar, Aundy; Achary, V. Mohan Murali; Ganesan, Prakash; Rathi, Neelmani; Singh, Asmita; Sahu, Kuleshwar Prasad; Lal, Shambhu Krishan; Das, T.K.; Reddy, Malireddy K.
Graphical abstract: Highlights: Glyphosate showed antifungal activity on Magnaporthe oryzae growth and sporulation. Glyphosate foliar spray suppressed blast disease on Osm EPSPS transgenic rice. Glyphosate enhanced the photosynthetic pigments such as chlorophyll and carotenoids in Osm EPSPS transgenic rice. Glyphosate activated defense related antioxidant enzymes like PAL, SOD and APX. Glyphosate repressed expression of Os PAD4, Os CERK1, Os NPR1.3, Os CEBiP, and Os FMO. Abstract: Weeds, pests, and pathogens are among the pre-harvest constraints in rice farming across rice-growing countries. For weed management, manual weeding and herbicides are widely practiced. Among the herbicides, glyphosate [N-(phosphonomethyl) glycine] is a broad-spectrum systemic chemical extensively used in agriculture. Being a competitive structural analog to phosphoenolpyruvate, it selectively inhibits the conserved 5-enolpyruvylshikimate-3-phosphate synthase (EPSPS) enzyme required for the biosynthesis of aromatic amino acids and essential metabolites in eukaryotes and prokaryotes. In the present study, we investigated the antifungal and defense elicitor activity of glyphosate against Magnaporthe oryzae on transgenic-rice overexpressing a glyphosate-resistance Os EPSPS gene (T173I + P177S; TIPS Osm EPSPS) for blast disease management. The glyphosate foliar spray on Osm EPSPS transgenic rice lines showed both prophylactic and curative suppression of blast disease comparable to a blasticide, tricyclazole. The glyphosate displayed direct antifungal activity on Magnaporthe oryzae as well as enhanced the levels of antioxidant enzymes and photosynthetic pigments in rice. However, the genes associated with phytohormones-mediated defense ( Os PAD4, Os NPR1.3, and Os FMO) and innate immunity pathway ( Os CEBiP and Os CERK1) were found repressed upon glyphosate spray. Altogether, the current study is the first report highlighting the overexpression of a crop-specific TIPS mutation in conjugation with glyphosate application showing potential for blast disease management in rice cultivation.